Word-by-word entrainment of speech rhythm during joint story building - Himberg, Tommi; Hirvenkari, Lotta; Mandel, Anne; Hari, Riitta (Frontiers in Psychology, 2015)
Movements and behaviour synchronise during social interaction at many levels, often unintentionally. During smooth conversation, for example, participants adapt to each others' speech rates. Here we aimed to find out to which extent speakers adapt their turn-taking rhythms during a story-building game. Nine sex-matched dyads of adults (12 males, 6 females) created two 5-min stories by contributing to them alternatingly one word at a time. The participants were located in different rooms, with audio connection during one story and audiovisual during the other. They were free to select the topic of the story. Although the participants received no instructions regarding the timing of the story building, their word rhythms were highly entrained (R ̅ = 0.70, p < 0.001) even though the rhythms as such were unstable (R ̅ = 0.14 for pooled data). Such high entrainment in the absence of steady word rhythm occurred in every individual story, independently of whether the subjects were connected via audio-only or audiovisual link. The observed entrainment was of similar strength as typical entrainment in finger-tapping tasks where participants are specifically instructed to synchronize their behaviour. Thus speech seems to spontaneously induce strong entrainment between the conversation partners, likely reflecting automatic alignment of their semantic and syntactic processes.